2005
DOI: 10.1167/iovs.04-0264
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Effects of Retinal Illuminance on Frequency Doubling Perimetry

Abstract: The results confirmed previous findings that FDT perimetry can be dramatically affected by variations in retinal illuminance. Application of a quantitative adaptation model provided guidelines for estimating effects of pupil diameter and lens density on FDT perimetry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…13 The temporal presentation for Gabor stimuli was a 600-msec increment in contrast, with abrupt onset and offset of 5-Hz counterphase square-wave flicker. A temporal frequency of 5 Hz was chosen to avoid effects of reduced retinal illumination that affect frequency-doubling perimetry, 40,41 and abrupt onset and offset were used to maximize the temporal contrast.…”
Section: Perimetrymentioning
confidence: 99%
“…13 The temporal presentation for Gabor stimuli was a 600-msec increment in contrast, with abrupt onset and offset of 5-Hz counterphase square-wave flicker. A temporal frequency of 5 Hz was chosen to avoid effects of reduced retinal illumination that affect frequency-doubling perimetry, 40,41 and abrupt onset and offset were used to maximize the temporal contrast.…”
Section: Perimetrymentioning
confidence: 99%
“…Swanson et al [33] have shown that FDT perimetry depends critically on retinal illuminance. In our sample of participants, pupil area ranged from 7.6 to 32.…”
Section: Pupil Areamentioning
confidence: 99%
“…10 The use of high temporal frequencies makes FDP susceptible to the effects of reduced retinal illumination, due to factors such as pupillary miosis and increase in lens density. 11 The goal of the present study was to design a new perimetric protocol, by using contrast sensitivity perimetry (CSP), 12 which could improve clinical management of glaucoma by building on findings of these earlier studies. We used a stimulus with a peak spatial frequency in the range used by FDP, but without the sharp stimulus edges and high temporal frequencies used in FDP.…”
mentioning
confidence: 99%